2000
DOI: 10.1088/0022-3727/33/18/309
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of laser-produced plasmas from boron nitride targets

Abstract: The interaction of 20 ns, 3 J laser pulses with solid boron nitride targets is studied spectroscopically in the wavelength range from 30 to 300 Å, and by taking pinhole pictures at short wavelengths. The experiments were carried out for different angles of incidence of the laser beam and as a function of the depth of the hole in the target. Typical temperatures are from 22 to 45 eV. It is observed that the heating of the plasma occurs at the bottom of the hole and that the hole is along the axis of the directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…34 In that work, the authors reported Q-switched ruby laser ͑I p ϳ 80 GW cm −2 ͒ ablation of boron, boron-carbide, and boron-nitride, and recorded space and time resolved EUV spectra, using a 10 ns gated detector. 35,36 As our results show, clear issues arise in using a constant N e value for spatiotemporal T ionz calculations. The first showed time resolved temperatures, 1 mm from the target surface, which displayed a slow rise in the T ionz profile, a relatively unresponsive peak followed by a slow fall.…”
Section: A T Ionz Dependency On N Ementioning
confidence: 87%
“…34 In that work, the authors reported Q-switched ruby laser ͑I p ϳ 80 GW cm −2 ͒ ablation of boron, boron-carbide, and boron-nitride, and recorded space and time resolved EUV spectra, using a 10 ns gated detector. 35,36 As our results show, clear issues arise in using a constant N e value for spatiotemporal T ionz calculations. The first showed time resolved temperatures, 1 mm from the target surface, which displayed a slow rise in the T ionz profile, a relatively unresponsive peak followed by a slow fall.…”
Section: A T Ionz Dependency On N Ementioning
confidence: 87%
“…and can be expressed in the form [11] V = α n (1) where α is a constant of proportionality and the exponent n depends on the material under investigation. In a recent article [12], we reported spectroscopic investigations of laser-produced plasmas from boron nitride targets. For pulsed lasers of nanosecond duration, boron nitride has a high mass ablation rate for intermediate fluences of the order of 1 kJ cm −2 , and hence investigations of plasma as a function of the drilled hole are readily performed.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen is a well-known contaminant in boron nitride systems, and has been observed in other ablation plasmas from similar boron nitride targets. 21 The primary band system A 3 P!X 3 P of the BN molecule, occurring between 340 and 400 nm, has relatively weak emission intensity compared to the atomic emission, and can be further masked by intense peaks of ionized boron at 345.1 nm and the second positive system C 3 P!B 3 P of excited molecular nitrogen N 2 from 350 nm to 400 nm. This has led to assumptions that the recombination reaction to form BN is not dominant in the plasma 11 and likely to occur at the substrate surface.…”
Section: Resultsmentioning
confidence: 99%